Validitas Pengembangan LKPD Berbasis Project Based Learning disertai Teka-Teki Silang pada Materi Kubus dan Balok Kelas IV Sekolah Dasar - Arlina Yuza; Susi Herawati; Hidayati Azkiya; Ade Madona (Universitas Negeri Padang, 2025)
The study aims to describe the validation results of Project Based Learning-Based Student Worksheets (LKPD) accompanied by Crossword Puzzles on Cube and Block Material for Grade IV Elementary School Students in the independent curriculum. This type of research is research and development (R & D) with the ADDIE development model: Analysis, Design, Development, Implementation, and Evaluation. The data in this study were processed quantitatively and described qualitatively. Validation was carried out by 3 experts, namely material, language, and media experts. The results showed that the results of the material expert validation on general aspects, current content, and completeness of content obtained an average value of 88.47% (valid criteria), validation of language experts on aspects of straightforwardness, communicativeness, dialogic and interactive, suitability and development of students, suitability with language rules, use of symbols and icons obtained an average value of 100.00% (very valid criteria), and the results of the media expert validation on aspects of appearance, use of letters and spaces, overall function obtained an average value of 87.72% (valid criteria). Thus, it can be concluded that the average percentage value of the validity of LKPD based on Project Based Learning accompanied by Crossword Puzzles on the Cube and Block Material for Grade IV Elementary School Students is 92.06% with the category of very valid.